THE GUIDELINES FOR ACADEMIC ADMINISTRATION ACCORDING TO FOUR IDDHIPĀDA PRINCIPLES BY EDUCATIONAL INSTITUTION ADMINISTRATORS UNDER THE KHON KAEN PROVINCIAL ADMINISTRATION ORGANIZATION - Lanwong, Jeerawat; Kangpheng , Samrit; Saikham, Sunthon (Journal of Buddhist Education and Research (JBER), 2024)
This research aimed to: 1. study the state of academic administration according to the Four Iddhipāda Principles by educational institution administrators 2. compare academic administration according to the Four Iddhipāda Principles by educational institution administrators, categorized by school size; 3. propose guidelines for academic administration according to the Four Iddhipāda Principles by educational institution administrators under the Khon Kaen Provincial Administration Organization. This study used a mixed-methods approach, incorporating both qualitative and quantitative research. The research instruments included a questionnaire and an interview, with a sample group of 265 school administrators and teachers under the Khon Kaen Provincial Administration Organization and 9 key informants, consisting of 5 administrators and 4 teachers, chosen through purposive sampling. Data analysis employed frequency, percentage, mean, standard deviation, F-tests, and descriptive content analysis. The research results were as follows: The state of academic administration according to the Four Iddhipāda Principles by school administrators under the Khon Kaen Provincial Administration Organization was generally at the highest level. The areas with the highest to lowest levels of practice were: administration according to Chanda, administration according to Citta (concentration), administration according to Vīmaṁsā and administration according to Viriya. Academic administration according to the Four Iddhipāda Principles by educational institution administrators, categorized by school size, showed no significant differences in overall practice or individual areas. The guidelines for academic administration according to the Four Iddhipāda Principles by educational institution administrators under the Khon Kaen Provincial Administration Organization suggest: emphasizing a participatory approach to academic administration; encouraging teachers to enjoy analyzing curricula and designing lesson plans; being committed to academic planning and promoting academic activities; creating a registry for teaching materials and innovation, and maintaining a question bank with thorough quality checks; joining and utilizing the results of educational supervision to support ongoing professional learning communities.